The Role of Music Education in Preserving Thai Cultural Heritage - อ่อนละมุล กฤษกร (Journal of Exploration in Interdisciplinary Methodologies (JEIM), 2024)
This paper explores the vital role of music education in preserving Thai cultural heritage, with a focus on traditional Thai music. By examining the historical development of music education in Thailand and the integration of traditional music into formal and community-based programs, the paper highlights how music education serves as a key mechanism for transmitting cultural knowledge and fostering national identity. The paper also addresses the challenges of modernity, globalization, and resource constraints while emphasizing the opportunities for innovation through technology, lifelong learning, and intergenerational engagement. Ultimately, the survival of traditional Thai music depends on collective efforts across government, educational institutions, and communities to ensure its continued relevance and vibrancy for future generations.